2009
DOI: 10.1021/ma8024909
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graft Density on Kinetics of Surface-Initiated ATRP of Polystyrene from Montmorillonite

Abstract: Here we report the kinetics of the surface-initiated atom transfer radical polymerization (ATRP) of styrene from the surface of functionalized montmorillonite clay as a function of graft density. Compared with analogous ATRP reactions with free initiator, we observe a seven-fold increase in the polymerization rate at the highest graft density, 1 chain/nm2, whereas bulk kinetics are recovered as the graft density is reduced. We hypothesize that this phenomenon is a consequence of local concentration heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 25 publications
4
83
0
Order By: Relevance
“…4.1c) as described in detail elsewhere. 117 We refer to MMT-graft-poly(styrene) homopolymer brushes as MMT-X, and MMT-graft-poly(styrene-block-t-butyl acrylate) block copolymer brushes as MBB-X-Y; X refers to polystyrene (PS) and Y to poly(tert-butyl acrylate) (PtBA) number-average molecular weight (M n ) in kDa. MBBs were annealed at 150 • C in vacuo for over 96 hours prior to being steady shear processed at 1 −s and 160-200 • C for 25 minutes on a TA Instruments ARES-LS1 strain controlled rheometer in the parallel plate geometry under N 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4.1c) as described in detail elsewhere. 117 We refer to MMT-graft-poly(styrene) homopolymer brushes as MMT-X, and MMT-graft-poly(styrene-block-t-butyl acrylate) block copolymer brushes as MBB-X-Y; X refers to polystyrene (PS) and Y to poly(tert-butyl acrylate) (PtBA) number-average molecular weight (M n ) in kDa. MBBs were annealed at 150 • C in vacuo for over 96 hours prior to being steady shear processed at 1 −s and 160-200 • C for 25 minutes on a TA Instruments ARES-LS1 strain controlled rheometer in the parallel plate geometry under N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A sonication probe was placed within one inch of the exterior of the reaction vessel for the duration of the experiment to maximize exfoliation without compromising the closed atmosphere. 140 t-Butyl acrylate (tB) and n-butyl acrylate (nB) were also synthesized as homopolymers from the fMMT surface at 75 • C and 65 • C respectively. nB samples initially showed poor polydispersity (PDI), so they were allowed to sonicate for 6 hours at 30 • C before reacting at 65 • C. …”
Section: Methodsmentioning
confidence: 99%
“…The grafting from method was employed by Behling et al to graft polymer chains on clay layers. 20 They studied the effect of grafting density of ATRP initiator on the kinetics of polymerization and reported that the proximity of initiator groups attached to the clay layers and the transitional metal catalyst increase the probability of activating macroinitiators and thereby increasing the rate of polymerization. The effect of the addition of Cloisite 30B on the atom transfer radical polymerization kinetics of styrene has also been studied by this group; an increase in the polymerization rate and polydispersity index of polystyrene chains was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In situ ATRP between individual silicate layers leads to the direct synthesis of dispersed silicate nanocomposites. After this study, several groups expanded the use of ATRP to prepare nanocomposites that contained polystyrene, [14,40] poly(ethyl acrylate), [17,18,21,41] poly(butyl acrylate), [14,21] PMMA, [14,20,42] and poly(2-hydroxyethyl methacrylate). [20] Although most of the efforts concentrated on homopolymers, there is also interest in block copolymer silicate nanocomposites because of their higher complex structure and technological importance.…”
Section: Polymer/clay Nanocomposites By Atrpmentioning
confidence: 99%
“…The best way to achieve such a control is by using living and controlled/living polymerization methods. [12] Various different living and controlled/living polymerization methods were used in the production of well-dispersed silicate layers, including atom transfer radical polymerization (ATRP), [13][14][15][16][17][18][19][20][21] nitroxide-mediated polymerization (NMP), [22,23] and reversible addition-fragmentation chain transfer (RAFT) polymerization, [24][25][26][27] ring-opening polymerization (ROP), [28][29][30][31][32][33] ring-opening metathesis polymerization (ROMP), [34][35][36] living cationic polymerization, [10,37] and living anionic polymerization ( Figure 1). [38,39] The common approach throughout the literature is to immobilize polymerization initiators in between the clay layers.…”
Section: Introductionmentioning
confidence: 99%